The Influence of the Government Internal Control System as a Mediator in the Influence of the Village Financial System Application on Fraud Prevention - Muhammad, Rahma Nazila; Afriady, Arif (Management Science Research Journal, 2024)
This study aims to analyze the influence of the Village Financial System (SISKEUDES) application in efforts to prevent fraud in village fund management and increase the influence of the Government Internal Control System (SPIP) as a mediation with a study in Kotabaru District, Karawang. This study is one type of quantitative research with path analysis. Data collection was carried out using a questionnaire, then the data was processed using the SMART PLS tool. The samples obtained from this study were intended for the head of financial management, head of planning, village secretary, and staff. The results of this study state that the SISKEUDES Application directly affects fraud prevention. Likewise, SPIP has a high mediation effect on fraud prevention in village management.